Instructional Material Adaptation & Recontextualization Model (IMARM): A Simulation Study - Febi Robianti (Indonesian Journal Publisher, 2025)
This study demonstrates the Instructional Material Adaptation & Recontextualization Model (IMARM) through a simulation using Andy Smith’s Native Trees from Seed. The simulation applies five IMARM stages—decoding, adaptation, recontextualization, reconstruction, and validation—to transform temperate-ecosystem content into materials relevant to Indonesia’s tropical context while integrating Islamic environmental ethics. The adapted module, “Harvesting Wisdom from a Single Seed,” illustrates IMARM’s capacity to modify terminology, examples, and instructional methods, and to reconstruct meaning aligned with local ecology, culture, and spiritual values. The findings indicate that IMARM is clear, flexible, and pedagogically effective, though it requires expert judgment and substantial time investment. Overall, IMARM shows strong potential for contextualizing global instructional resources and supporting the development of localized Islamic-ecological curricula, with further research recommended for classroom implementation, cross-disciplinary use, and digital tool development.